2013
DOI: 10.1186/1471-2431-13-202
|View full text |Cite
|
Sign up to set email alerts
|

Is early detection of abused children possible?: a systematic review of the diagnostic accuracy of the identification of abused children

Abstract: BackgroundEarly detection of abused children could help decrease mortality and morbidity related to this major public health problem. Several authors have proposed tools to screen for child maltreatment. The aim of this systematic review was to examine the evidence on accuracy of tools proposed to identify abused children before their death and assess if any were adapted to screening.MethodsWe searched in PUBMED, PsycINFO, SCOPUS, FRANCIS and PASCAL for studies estimating diagnostic accuracy of tools identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 45 publications
(104 reference statements)
4
63
0
1
Order By: Relevance
“…A recent case–control study of children aged <3 years admitted with a burn showed that almost one-third of children with burns had been referred to social services because of child protection (CP) concerns by their sixth birthday 10. Recent systematic reviews have shown a lack of effective, validated, generic ED tools for identifying childhood maltreatment 11 12. An injury-specific tool may be more effective, as in other disciplines, for example, for identifying head injury 13…”
Section: Introductionmentioning
confidence: 99%
“…A recent case–control study of children aged <3 years admitted with a burn showed that almost one-third of children with burns had been referred to social services because of child protection (CP) concerns by their sixth birthday 10. Recent systematic reviews have shown a lack of effective, validated, generic ED tools for identifying childhood maltreatment 11 12. An injury-specific tool may be more effective, as in other disciplines, for example, for identifying head injury 13…”
Section: Introductionmentioning
confidence: 99%
“…The RMNCH and nutrition reviews relied primarily on five recent overviews of reviews, including the Lancet 2014 Every Newborn series, (13) (21) A meta-analysis of education programmes was conducted to determine non-cognitive developmental benefits of parenting and early childhood education programmes, as this information was not available in existing systematic reviews. The maltreatment review updated the Lancet 2009 series for prevention of child maltreatment (22) and a systematic review of reviews of interventions to reduce child maltreatment, (23) in addition to a review of 14 recent reviews of maltreatment prevention interventions, including home visiting, (24)(25)(26), parenting-training programmes, (27,28) sexual abuse prevention programmes, (29,30) universal campaigns to prevent physical abuse,(31) behavioural and counseling interventions,(32) detection of child maltreatment, (33) and three review studies on prevention of child maltreatment. (34)(35)(36) The social protection review examined five systematic reviews that focused on the effects of social programmes, including conditional and unconditional cash transfers and microcredit schemes.…”
Section: Comment [Pb1]mentioning
confidence: 99%
“…), and three studies that deal with abuse alone (Bailhache et al. ; Kalmakis & Chandler ; Kristman‐Valente & Wells ). Finally, it was determined that there was only one study (Ji & Finkelhor ) that dealt with physical abuse.…”
Section: Discussionmentioning
confidence: 99%